2009
DOI: 10.1021/jp907633g
|View full text |Cite
|
Sign up to set email alerts
|

Perylene Tetracarboxydiimide as an Electron Acceptor in Organic Solar Cells: A Study of Charge Generation and Recombination

Abstract: We study charge generation and recombination in organic solar cells that utilize perylene tetracarboxydiimide (PDI) as an electron acceptor and a conjugated polymer as an electron donor. PDI is a promising electron acceptor because of its strong red absorption, LUMO well placed to accept electrons from many conjugated polymers, and good electron mobility. However, we find that, when PDI is finely dispersed in a conjugated polymer, the device efficiency is severely limited by very fast bimolecular charge recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 140 publications
(165 citation statements)
references
References 35 publications
5
159
0
Order By: Relevance
“…83,84 Of similar interest are polymers carrying pendent fullerenes, 85 although they tend to suffer from aggregative effects of C 60 rather than self-assembly, 86 or linear main-chain polymers based on C 60 as a monomer, which seem to have displayed morphologies more appropriate to charge collection and transfer. 87 Further work on other acceptors such as perylene, notably perylene tetracarboxydiimide (PDI), 88,89 the poly(benzimidazobenzophenanthroline) ladder (BBL), 90 and units based on 9,9'-bifluorenylidene, 91 conversely, have shown that fullerene may not be necessary.…”
Section: Figurementioning
confidence: 99%
“…83,84 Of similar interest are polymers carrying pendent fullerenes, 85 although they tend to suffer from aggregative effects of C 60 rather than self-assembly, 86 or linear main-chain polymers based on C 60 as a monomer, which seem to have displayed morphologies more appropriate to charge collection and transfer. 87 Further work on other acceptors such as perylene, notably perylene tetracarboxydiimide (PDI), 88,89 the poly(benzimidazobenzophenanthroline) ladder (BBL), 90 and units based on 9,9'-bifluorenylidene, 91 conversely, have shown that fullerene may not be necessary.…”
Section: Figurementioning
confidence: 99%
“…[3][4][5][6][7] On the other hand it has been recently found that excimer formation can also have a positive effect on the properties of organic materials, facilitating processes such as singlet fission. [8][9][10][11][12] For this reason, the understanding of the excimer formation dynamics in molecular aggregates is of fundamental importance for the development of novel materials that can be employed in organic electronics or photovoltaics applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these stabilized intermolecular states are likely to act as traps for diffusive excitons. 7 In case of P3HT:PDI-1 and P3HT:PDI-3, the low energy range of the PL emission between 1.3 and 1.6 eV (Figure 4.b) shows essentially the same decay characteristics as the high-energy part, indicating, that this range of the spectra is governed by PDI emission as well. In case of P3HT:PDI-2, however, the PL decays even slower than in the pristine P3HT film.…”
Section: Resultsmentioning
confidence: 79%
“…6 In case of planar PDI, however, morphologies with micrometer-sized crystallites have been reported for several blend material systems. [7][8][9][10] Furthermore, there is experimental evidence that charge generation in PDI-based solar cells is limited by geminate losses at the interfaces. Interfacial CT states are assumed to play a key role in the charge generation process, as they may either dissociate into free charges or give rise to geminate recombination, thereby reducing the photoconversion efficiency (PCE).…”
Section: Introductionmentioning
confidence: 99%